Recurrent activating STAT5B N642H mutation in myeloid neoplasms with eosinophilia - Cross, Nicholas C. P.; Jawhar, Mohamad; Naumann, Nicole; Lübke, Johannes; Reiter, Andreas (Leukemia, 2019)
Determining the underlying cause of persistent eosinophilia is important for effective clinical management but remains a diagnostic challenge in many cases. We identified STAT5B N642H, an established oncogenic mutation, in 27/1715 (1.6%) cases referred for investigation of eosinophilia. Of the 27 mutated cases, a working diagnosis of hypereosinophilic syndrome (HES; n = 7) or a myeloid neoplasm with eosinophilia (n = 20) had been made prior to the detection of STAT5B N642H. Myeloid panel analysis identified a median of 2 additional mutated genes (range 0-4) with 4 cases having STAT5B N642H as a sole abnormality. STAT5B N642H was absent in cultured T cells of 4/4 positive cases. Individuals with SF3B1 mutations (9/27; 33%) or STAT5B N642H as a sole abnormality had a markedly better overall survival compared to cases with other additional mutations (median 65 months vs. 14 months; hazard ratio = 8.1; P < 0.001). The overall survival of STAT5B-mutated HES cases was only 30 months, suggesting that these cases should be reclassified as chronic eosinophilic leukemia, not otherwise specified (CEL-NOS). The finding of STAT5B N642H as a recurrent mutation in myeloid neoplasia with eosinophilia provides a new diagnostic and prognostic marker as well as a potential target for therapy.
Published online: 20 December 2018
Gesehen am 19.11.2019